Identities amongst the two loop partial amplitudes of Yang-Mills theory - David C. Dunbar (Journal of High Energy Physics, 2023)
Abstract We characterise possible identities among the two-loop partial amplitudes of gluon scattering in Yang-Mills theory. We use known amplitudes in an exhaustive search to identify potential new relations. We find two candidate relations which may extend to all-n amplitudes.